The Impact of Human Capital on Improving Marketing Performance: A Field Study in Yemeni Private Universities in the Capital Municipality of Sana'a - Abdulatef Musleh Mohammed Ayedh; Khaled Ahmed Ali Al-Qudaimi (University of Science and Technology, Sana’a, Yemen, 2025)
This study aimed to determine the impact of human capital on improving marketing performance in Yemeni private universities in the Capital Municipality - Sana'a. The study adopted a descriptive-analytical research approach. The study population included heads of academic and administrative departments, general secretaries, directors of departments and their deputies, deans of colleges and their deputies, and university presidents and their deputies, totaling 437 individuals. A proportional stratified random sample of 205 individuals was selected. Data were collected using a questionnaire, and the data were entered, coded, and processed using SPSS 23. Descriptive statistical methods were used to measure the study's objectives, and structural equation modeling (SEM) was employed via the Smart PLS statistical program to test the main and subsidiary hypothesis paths. The results of the study revealed that the level of marketing performance in the universities under study was high across all dimensions, and human capital was also available at a high level across all dimensions. The results also showed a statistically significant direct impact of human capital, with all its dimensions combined, on improving the marketing performance of the universities under study. The study recommends the importance of focusing on human capital in all its dimensions due to its impact on improving marketing performance in Yemeni private universities in the Capital Municipality - Sana'a.